The effect of transcranial direct current stimulation on frontal alpha asymmetry and visuospatial attention in food-reward contexts: a triple-blind randomized sham-controlled study - Atakan M. Akil; Renáta Cserjési; Dezső Németh; Tamás Nagy; Zsolt Demetrovics; H. N. Alexander Logemann (BMC Psychology)
Abstract Background Research indicates a connection between right frontal brain activity dominance and the inhibitory system. However, the underlying brain mechanism regarding attentional control remains unclear. In this preregistered experiment, we explored the association between frontal alpha asymmetry (FAA) — which is an electrophysiological measure of the difference in alpha power between the left and right dorsolateral prefrontal cortex — and the behavioral and brain activity components of attentional bias and disengagement, as observed in a visuospatial cueing (VSC) task. Method We used a triple-blind randomized sham-controlled design with 65 (M age = 23.93; SD age = 6.08; 46 female) healthy humans. Participants’ resting-state EEG was recorded to calculate FAA scores before and after 2 mA anodal transcranial direct current stimulation (tDCS) to the right frontal site for 20 min. They also completed a VSC task with neutral and intrinsic reward-associated (food) conditions. Results Results indicated no impact of tDCS on FAA or behavioral attentional bias and disengagement. Exploratory analyses revealed tDCS-induced attentional bias for rewards, as detected in enhanced Late Directing Attention Positivity and P1 effect. However, these effects did not translate into observable behavioral changes. Conclusion The enhanced attentional bias may result from tDCS-induced enhancement of top-down attentional orienting to spatial locations associated with reward-related stimuli, potentially mediated by noradrenergic mechanisms.